Fasceite necrotizante cervical secundária a amigdalite bacteriana - Zilberstein, Bruno (2005)
Necrotizing fasciitis is a severe and potentially fatal soft tissue infection, but involvement of the head and neck is rare. We report on 4 cases of cervical necrotizing fasciitis arising from tonsillitis. One patient was diabetic and one had received steroids before disease development. One patient developed acute respiratory failure and died of septic shock. Three patients recovered, helped by early recognition, aggressive surgical intervention, appropriate broad-spectrum antibiotics, and supportive therapy. The common bacteria found in all abscess samples were Streptococcus sp., but mixed flora with anaerobic organisms was seen in all but 1 case. Tonsillitis and peritonsillar abscess must be suspected as a cause of cervical necrotizing fasciitis and a successful result can be achieved with immediate aggressive treatment.